The Safety and Efficacy of Sacral Neuromodulation on Refractory Urgency Urinary and Fecal Incontinence in Iraqi Patients (Medico Legal Update, 2021)
Background: Urinary urgency incontinence is characterized by symptoms of involuntary loss of urine thatpreceded or accompanied by sudden desire to void. Fecal incontinence is defined as involuntary passage ofstool through the anus. It may vary from soiling to complete evacuation. This involuntary loss of feces, flatusor urge incontinence adversely affects quality of life.Objectives: To evaluate the efficacy and safety of sacral neuromodulation on these pathologies.Method: Following a detailed investigation, 21 patients with either urinary incontinence, or both urinaryand fecal, who did not respond to medical and behavioral treatment were offered the sacral neuromodulationtherapy and followed for at least 12 months post implant regarding response and development of complicationif any found.Results: In the period from November 2015 to May 2017. The unit of neurogenic bladder and neuromodulationin surgical subspecialty hospital, medical city complex had implanted 21 Patients with urinary incontinencewere using from (4-17) pads/day (mean of 10.5/day) presacral neuromodulation which were declinedsignificantly to (0-3) pads/day (mean of 2.2/day).From the eighteen patients who presented with fecal incontinence after the implantation of sacralneuromodulation interstim 11 permanent devices only four remained incontinent .and from the nine patientswho presented with erectile dysfunction only two remained impotent.Conclusion: The use of Sacral Neuromodulation in Iraqi patients with Urinary and Fecal Incontinence issafe and effective